Effect of boron doped fullerene C-60 film coating on the electrochemical characteristics of silicon thin film anodes for lithium secondary batteries - Arie, Arenst Andreas; Lee, Joong Kee (ELSEVIER SCIENCE SA, 2011)
In this work, boron doped fullerene (B:C-60) films were prepared by the radio frequency plasma assisted thermal evaporation technique for use as a coating material for the silicon thin film anode in lithium secondary batteries. Raman and XPS analyses revealed that the boron atoms were well inserted into the fullerene film lattices. The effect of the B:C-60 film on the electrochemical characteristics of the silicon thin film was studied by charge-discharge tests, electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The B:C-60 coated silicon film exhibited a high reversible capacity of more than 1200 mAh g(-1) when cycled 50 times between 0 and 2 V at a current density of 1200 mu A cm(-2) (1.5 C). The film also showed good rate capacity at different current densities and a more improved coulombic efficiency of 87.7% in the first cycle in comparison with that of the C-60 coated film electrode. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: CARBON; INSERTION